How to deal with babies - Powell, Richard, 1957-; Snow, Alan ([Mahwah, N.J.] : Watermill Press, 1990)
A boy describes his adjustment to the arrival of his baby sister and how he learned to get along with her and enjoy her company.
Keywords: Infants -- Juvenile literature; Infants -- Development -- Juvenile literature; Babies; Brothers and sisters